ATR activation and replication fork restart are defective in FANCM-deficient cells. - Schwab, R; Blackford, A; Niedzwiedz, W (2010)
Fanconi anaemia is a chromosomal instability disorder associated with cancer predisposition and bone marrow failure. Among the 13 identified FA gene products only one, the DNA translocase FANCM, has homologues in lower organisms, suggesting a conserved function in DNA metabolism. However, a precise role for FANCM in DNA repair remains elusive. Here, we show a novel function for FANCM that is distinct from its role in the FA pathway: promoting replication fork restart and simultaneously limiting the accumulation of RPA-ssDNA. We show that in DT40 cells this process is controlled by ATR and PLK1, and that in the absence of FANCM, stalled replication forks are unable to resume DNA synthesis and genome duplication is ensured by excess origin firing. Unexpectedly, we also uncover an early role for FANCM in ATR-mediated checkpoint signalling by promoting chromatin retention of TopBP1. Failure to retain TopBP1 on chromatin impacts on the ability of ATR to phosphorylate downstream molecular targets, including Chk1 and SMC1. Our data therefore indicate a fundamental role for FANCM in the maintenance of genome integrity during S phase.